Seeking Information for School Purposes on the Internet - Holly Gunn; Gary Hepburn (The Canadian Network for Innovation in Education (CNIE), 2003)
This paper reports the findings of a study undertaken in four Nova Scotia public schools of twelfth grade students' information seeking strategies when they use the Internet as an information source. Various Nova Scotia Department of Education curriculum documents hold high expectations of students' information seeking strategies when using the Internet for educational purposes. This study looks at whether these expectations are being realized. The results include the students' use of specific information seeking strategies, knowledge of World Wide Web Search engines, as well as how students acquired their Internet information seeking knowledge, and students' perceptions of their ability to locate information on the Internet. The results of the study have important implications for Internet education and the role of information professionals in public schools.